An assessment of the smart manufacturing activities at the National Institute of Standards and Technology Engineering Laboratory : fiscal year 2017 (Consensus study report., 2017)
"The mission of the Engineering Laboratory (EL) of the National Institute of Standards and Technology (NIST) is to 'promote U.S. innovation and industrial competitiveness by advancing measurement science, standards, and technology for engineered systems in ways that enhance economic security and improve quality of life.' To support this mission the EL has developed thrusts in smart manufacturing, construction, and cyberphysical systems; in sustainable and energy-efficient manufacturing materials and infrastructure; and in disaster-resilient buildings, infrastructure, and communities. The technical work of the EL is performed in five divisions - Intelligent Systems, Materials and Structural Systems, Energy and Environment, Systems Integration, and Fire Research - and in two offices - the Applied Economics Office and the Smart Grid Program Office. At the request of the acting director of NIST, the National Academies of Sciences, Engineering, and Medicine assesses the scientific and technical work performed by the NIST Engineering Laboratory (EL). This publication reviews technical reports and technical program descriptions prepared by NIST staff summarizes the findings of the authoring panel"--Publisher's description